2006
DOI: 10.1007/s11664-006-0162-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reaction time on mechanical strength of the interface formed between the Sn-Zn(-Bi) solder and the Au/Ni/Cu bond pad

Abstract: In this work, the shear strengths and the interfacial reactions of Sn-9Zn, Sn-8Zn-1Bi, and Sn-8Zn-3Bi (wt.%) solders with Au/Ni/Cu ball grid array (BGA) pad metallization were systematically investigated after extended reflows. Zncontaining Pb-free solder alloys were kept in molten condition (240°C) on the Au/electrolytic Ni/Cu bond pads for different time periods ranging from 1 min. to 60 min. to render the ultimate interfacial reaction and to observe the consecutive shear strength. After the shear test, frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…4). As a result, the forces became higher with extended reflow because of the larger sheared area [17]. Detailed cross-sectional studies were carried out to investigate the relationship between the shear strength and the interfacial morphologies of the solder with the pad metallizations.…”
Section: Resultsmentioning
confidence: 99%
“…4). As a result, the forces became higher with extended reflow because of the larger sheared area [17]. Detailed cross-sectional studies were carried out to investigate the relationship between the shear strength and the interfacial morphologies of the solder with the pad metallizations.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed it has been reported before that bulk solder strength can increase with thermal aging time when the aging temperature is no more than 160°C 25 or with reflow duration within a relatively short duration. 27 There has been no sound explanation for this increase so far, but we believe that it could be explained by increased dissolution of metallization metals into the bulk solder. Upon cooling, a greater volume fraction of IMC particles will precipitate out in the solder matrix, leading to an increase in solder strength.…”
Section: Effect Of Electromigration On the Mechanical Properties Of Smentioning
confidence: 85%
“…Most previous results have reported that this phenomenon deteriorates the interfacial mechanical properties with increasing thickness of the IMC layers. [5][6][7] However, for some solder joints, increasing thickness of the IMC layers is not the sole reason for the decrease in mechanical properties; for example, the formation of the Cu 3 Sn layer and voids at the interface can also strongly deteriorate the mechanical properties of the solder joints.…”
Section: Introductionmentioning
confidence: 99%